The Analysis Study of Effectiveness of Corticosteroid and Lidocaine Injection for Hip Osteoarthritis: A Ten Years Systematic Review - Efo Dika Permana; Hapif; Alifia Rifki Rimanda (The Indonesian Journal of General Medicine, 2025)
Background: Hip osteoarthritis (OA) is a common cause of chronic pain and disability that affects millions of people. It happens when the hip joint wears down over time, making movement painful and difficult. This systematic review aims to evaluate current literatures about the effectiveness of corticosteroid and lidocaine injection on hip osteoarthritis. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2015 to 2025. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: Corticosteroid and lidocaine injections remain a valuable option for short-term pain relief in hip OA, particularly for patients with synovitis or effusion. However, concerns regarding long-term joint health, infection risks, and diminishing efficacy over time suggest that these injections should be used judiciously.